Evaluation of the Potential of High-Performance Liquid Chromatography–Inductively Coupled Plasma–Mass Spectrometry for the Determination of Chemical Warfare Agents and Their Toxic Degradation Products - Monika Kuligowska; Slawomir Neffe (Molecules, 2024)
The determination of chemical warfare agents (CWAs) and their toxic degradation products (DPs) has become increasingly important for public and military safety in recent years. We focused on assessing the possibility of the HPLC-ICP-MS analytical technique to verify the provisions of the Chemical Weapons Convention. This technique enables the identification and determination of minimal concentrations (ppt range) of elements in various matrices. This fact is important for the determination of CWAs and other highly harmful compounds, even small amounts of which can have serious consequences for living organisms. We have critically analysed the results of scientific research on the identification and quantitative determination of extremely toxic organophosphorus, organosulfur and organoarsenic CWAs, their derivatives and their degradation products using high-performance liquid chromatography (HPLC) coupled with inductively coupled plasma–mass spectrometry (ICP-MS).